PENINGKATAN KEMAMPUAN SPEAKING BAHASA INGGRIS PADA “SOBAT ABROAD ENGLISH CLUB” DENGAN MENGGUNAKAN PLATFORM GOOGLEMEET - Suswanto Ismadi Megah; Eka Wilany; Desi Surlitasari Dewi (ASOSIASI IDEBAHASA KEPRI, 2023)
English speaking is urgently needed in the industrial era, especially in Batam City which is essential for international communication between countries so as to facilitate people who want to travel to abroad. ‘Sobat Abroad English Club’ is a English club which prepares English students to continue their studies in foreign countries. The club needs a guide to improve their English speaking via Googlemeet. The, they collaborate LPPM Unrik to improveEnglish speaking skills with the googlemeet platform. All service activities are carried out within a span of 5 months (Juli 2022-Desember 2022). The results showed that the post-test results got a conclusion that the improvement of 'speaking' ability of member of Sobat abroad was good with an average score of 73.9, while the lowest score was 68.3 and the highest score was 81.6. The lowest average score is 68.3 and the highest is 73.9 with an average of 73.9. So the average result of the pre-test and post-test scores is 79.4, Thus, the achievement value of members of ‘Sobat Abroad English Club’ abroad was significantly improved and categorized as ‘good’. Keywords— Improving, English Speaking, Googlemeet